The Translatability of Interjections: A Case Study of Arabic-English Subtitling - Thawabteh, Mohammad (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2010)
This paper examines the translatability of Arabic interjections into English subtitling, illustrated with a subtitled Egyptian film, State Security subtitled by Arab Radio and Television (ART). Theoretical framework regarding both Audiovisual Translation (AVT) and interjections is first discussed. The significance of interjections is approached from the perspective of technical and translation paradigms. The study shows that although technical issues limit the subtitler’s choices, they have very little to do with translating interjections because they are typically short words. With regard to translation, the study shows that the subtitler may opt for three major translation strategies: 1) an avoidance of source language (SL) interjection whereby a SL interjectional utterance is translated into a target language (TL) interjection-free utterance; 2) a retention of SL interjection in which SL interjection is rendered into a TL interjection; and 3) an addition of interjection whereby SL interjection-free utterance is translated into a TL interjection.